The Elohist: A 7th-Century bce Theological Tradition - Gnuse, Robert Karl (Biblical theology bulletin, 2012)
The Elohist Pentateuchal tradition may be dated to the 7th and 6th centuries bce in the cult center of Bethel as a theological response to the destruction of Samaria and the exile of Israelites in the north in 722 bce. If this is true, then significant theological themes may be perceived in these texts that address the religious needs and the question of identity for Israelite exiles. Eventually these Elohist texts will be absorbed by the Yahwist Historian in the late 6th century bce.